2014
DOI: 10.1021/la404660f
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Multilayers on PTMSP as Asymmetric Membranes for Gas Separations: Langmuir–Blodgett versus Self-Assembly Methods of Anchoring

Abstract: Polyelectrolyte multilayers derived from poly(diallyldimethylamonium chloride) and poly(sodium 4-styrenesulfonate) have been deposited onto poly[1-(trimethylsilyl)-1-propyne] (PTMSP) with anchoring layers formed by Langmuir-Blodgett and self-assembly methods. Using gas permeation selectivity as a basis for judging the efficacy of each anchoring method, we have found that similar CO2/N2 selectivities (ranging from 110 to 140) could be achieved by both methods and that their permeances were also similar. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Because self‐assembly methods are much simpler (e. g., adsorbing a monolayer of branched poly(ethyleneimine), b ‐PEI onto PTMSP), we carried out a detailed study to determine whether there were any advantages to the more laborious LB method. Thus, a Langmuir‐Blodgett monolayer of a poly(1‐octadecene‐alt‐N,N,N‐trimethylammonium‐N‐ethylmaleimide) chloride (POMTMA) was compared with a self‐assembled monolayer of branched poly(ethyleneimine) ( b ‐PEI) as anchor layers, using PEMs formed from PDDA and PSS as a test case (Figure ) . In this study, we found that similar CO 2 /N 2 selectivities (ranging from 110 to 140) and similar permeances were obtained using both types of anchors.…”
Section: Hyperthin Polyelectrolyte Multilayers For Gas Separationsmentioning
confidence: 54%
“…Because self‐assembly methods are much simpler (e. g., adsorbing a monolayer of branched poly(ethyleneimine), b ‐PEI onto PTMSP), we carried out a detailed study to determine whether there were any advantages to the more laborious LB method. Thus, a Langmuir‐Blodgett monolayer of a poly(1‐octadecene‐alt‐N,N,N‐trimethylammonium‐N‐ethylmaleimide) chloride (POMTMA) was compared with a self‐assembled monolayer of branched poly(ethyleneimine) ( b ‐PEI) as anchor layers, using PEMs formed from PDDA and PSS as a test case (Figure ) . In this study, we found that similar CO 2 /N 2 selectivities (ranging from 110 to 140) and similar permeances were obtained using both types of anchors.…”
Section: Hyperthin Polyelectrolyte Multilayers For Gas Separationsmentioning
confidence: 54%
“…11.5 nm). 15 nm, all of the membranes investigated [i.e., (PSS-PAH) 10.5 , (PSS-1c) 13.5 , (PSS-1b) 12.5 and (PSS-1a) 11.5 ] exhibited similar permeation selectivities (ca. Addition of three bilayers of PSS-1c to produce (PSS-1c) 13.5 led to a further reduction in permeability and an increase in permeation selectivity.…”
mentioning
confidence: 93%
“…Polyelectrolyte multilayers that were fabricated from 13.5 bilayers of PSS and PAH (i.e., [PSS-PAH] 13 To assess their permeability properties, hyperthin PEMs made from PSS plus PAH, 1a, 1b or 1c were deposited onto cast films of poly[1-(trimethylsilyl)-1-propyne] (PTMSP) that were surface-modified b-PEI. 13 In Table 1 are listed the permeances (P/l) that were observed with respect to H 2 and N 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain ultrathin layers of PIM, we considered the Langmuir-Blodgett (LB) technique [8] which can be used for the deposition of polymeric layers on top of different kinds of supports to produce composite membranes.B yu sing this approach,LBfilms formed by different surfactants have been previously deposited onto poly[1-(trimethylsilyl)-1-propyne] (PTMSP) substrates to enhances electivities for H 2 /CO 2 [9] and CO 2 /N 2 [10] separations. Ultrapermeable PTMSP films have also been used as support for the deposition of metal-organic covalentn etworks by chemical vapor deposition for gas separation membranes.…”
mentioning
confidence: 99%